SKILLS AND KNOWLEDGE DEMAND FOR INDUSTRY READY TOWN PLANNING GRADUATES - Rashid, Kushairi; Kamal, Kamarul’ain (PEOPLE: International Journal of Social Sciences, 2019)
Emerging of new technologies skills are fundamentally changing how urban planners think, analyses and determine development decision. Application of mobile technologies and increase of public awareness are new challenges that affect traditional planning procedures and design process, resulting widening knowledge and skills gaps between town planning graduates and demand by the industry. This poses questions on the graduates’ capability to meet the job market demands especially on handling town planning related tasks. Therefore, this research endeavours to determine current knowledge and skill demands among planning agencies by using quantitative research approach as main research strategy. Findings of the study suggest Spatial Information System, Online Mapping, Crowd Sourcing technology along with instilling collaborative and multidisciplinary soft skills, in the new syllabus are considered vital. Thus the implementation of a revised syllabus which take into consideration both knowledge and skills components, would surely offers well equip market ready town planning